The Dissatisfaction with Body Shape with social anxiety In Early Adult Women in Kupang City - Agnesta Farida Gamelia; M. K. P. Abdi Keraf; Theodora Takalapeta (Journal of Health and Behavioral Science, 2023)
Body shape dissatisfaction is a negative evaluation that the individual makes of thoughts and judgments about his own body. One of the factors causing dissatisfaction with body shape in women is due to a deep feeling of dissatisfaction with themselves and always comparing their body shape with that of other individuals. Social anxiety is a situation where the individual feels fearful of being in public because of the discomfort or worry of being judged or criticized while in a public place, so that the individual becomes embarrassed and thinks negatively about himself. The aim of this study was to discover the relationship between body dissatisfaction (measured by the Body Shape Questionnaire) and social anxiety in early adult women (measured by the Liebowitz Social Anxiety Scale). This type of research is a quantitative research that uses descriptive methods. 392 women aged between 18 and 27 years participated in the study. The results of the correlational analysis show that there is a significant positive relationship between these two variables. The result is r 0.367 with a significance value of 0.000 < 0.05.